2022
DOI: 10.3390/fishes7010022
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach Evaluating Soybean Meal-Induced Enteritis in Rainbow Trout Oncorhynchus mykiss

Abstract: This study evaluated a diverse range of markers of feeding stress to obtain a more precise assessment of the welfare of rainbow trout in relation to inadequate husbandry conditions. A feeding stress model based on dietary soybean meal was employed to identify suitable minimally invasive “classical” stress markers, together with molecular signatures. In a 56-day feeding experiment, rainbow trout were fed diets containing different levels of soybean meal. The impact of these different soybean meal diets on rainb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…The novelty of the present study was a paradigm shift in that it evaluated the response of fish to graded levels of PBM and BSFM, either singly or in combination, to replace the protein from vegetable sources in fishmeal-free diets, including substantial levels of soybean meal (SBM). It is well known that in salmonids, feeding diets high in vegetable protein sources, particularly SBM, can result in impaired growth performance and gut disorders [33,[65][66][67]. This has recently also been confirmed in this research, as previously reported by Randazzo et al [11].…”
Section: Growth Performancesupporting
confidence: 88%
See 2 more Smart Citations
“…The novelty of the present study was a paradigm shift in that it evaluated the response of fish to graded levels of PBM and BSFM, either singly or in combination, to replace the protein from vegetable sources in fishmeal-free diets, including substantial levels of soybean meal (SBM). It is well known that in salmonids, feeding diets high in vegetable protein sources, particularly SBM, can result in impaired growth performance and gut disorders [33,[65][66][67]. This has recently also been confirmed in this research, as previously reported by Randazzo et al [11].…”
Section: Growth Performancesupporting
confidence: 88%
“…Moreover, the knowledge on the involvement of dietary protein/amino acids in modulating the primary and secondary stress response is still quite unexplored [27,98,99]. Previous studies have shown that plant-based diets induce chronic stress or reduced stress tolerance in rainbow trout [33,100,101], but little or no information is available on the stress response to diets containing insect or poultry by-product meals. In this study, the serum cortisol level did not differ among dietary treatments and was close to the basal levels reported for rainbow trout, indicating no primary stress response [102].…”
Section: Fish Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of leukocyte and thrombocyte markers was also evaluated by real-time quantitative PCR (RT-qPCR) using the LightCycler 96 System (Roche, Germany) in combination with the SensiFAST SYBR No-ROX Kit (Bioline, London, UK). We profiled the marker genes encoding sptb in RBCs (5’-CACGCATCAAAACCCTAACAGAT-3’, sense; 5’-TGATGAGCATGCGTCCATCCC-3’, antisense), cd8 on cytotoxic T cells (5’-TTTTGTCAAGAAACTCTCCAACTGA-3’, sense; 5’-AATCACCATGTTGCTCTTAGTCTT-3’, antisense), cd4 on T-helper cells (5’-ATCTCCTCAACAGGGGCTGAAG-3’, sense; 5’-CTGTCTTTCCACTCTGGATCTAT-3’, antisense), igm on B cells ( 54 ), and cd41 on thrombocytes ( 54 ). Eef1a1 and rps5 served as reference genes to normalize the expression data.…”
Section: Methodsmentioning
confidence: 99%
“…Soybean meal has a high protein concentration relative to other plant sources (~40% dry weight [DW]), has a relatively good balance of essential amino acids, and is typically inexpensive (Booman et al 2018;Agboola et al 2022). While soybean meal has already been incorporated into many commercial fish diets, high inclusion rates (above 25%) in carnivorous finfish feeds are associated with reduced protein digestibility, intestinal inflammation (enteritis), and reduced growth efficiency (Seibel et al 2022). Conventional soybean meal contains anti-nutritional factors, such as saponins, protease inhibitors, and lectins, which cause proximal intestine inflammation and reduce the overall efficiency of nutrient digestion and absorption from feeds (Agboola et al 2022).…”
Section: Introductionmentioning
confidence: 99%